Evolutionary effects of nitrogen are not easily predicted from ecological responses. Issue 11 (13th November 2022) - Waterton, Joseph; Hammond, Mark; Lau, Jennifer A.
Abstract: Premise: Anthropogenic nitrogen (N) addition alters the abiotic and biotic environment, potentially leading to changes in patterns of natural selection (i.e., trait–fitness relationships) and the opportunity for selection (i.e., variance in relative fitness). Because N addition favors species with light acquisition strategies (e.g., tall species), we predicted that N would strengthen selection favoring those same traits. We also predicted that N could alter the opportunity for selection via its effects on mean fitness and/or competitive asymmetries. Methods: We quantified the strength of selection and the opportunity for selection in replicated populations of the annual grass Setaria faberi (giant foxtail) growing in a long‐term N addition experiment. We also correlated these population‐level parameters with community‐level metrics to identify the proximate causes of N‐mediated evolutionary effects. Results: N addition increased aboveground productivity, light asymmetry, and reduced species diversity. Contrary to expectations, N addition did not strengthen selection for trait values associated with higher light acquisition such as greater height and specific leaf area (SLA); rather, it strengthened selection favoring lower SLA. Light asymmetry and species diversity were associated with selection for height and SLA, suggesting a role for these factors in driving N‐mediated selection. The opportunity for selection was not influenced by N addition but was negatively associated with species diversity. Conclusions: Our results indicate that anthropogenic N enrichment can affect evolutionary processes, but that evolutionary changes in plant traits within populations are unlikely to parallel the shifts in plant traits observed at the community level.